2021
DOI: 10.1111/fcp.12584
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of CREB‐BDNF signaling pathway in neuroprotective effects of minocycline against alcohol‐induced neurodegeneration: molecular and behavioral evidences

Abstract: Abuse of alcohol triggers neurodegeneration in human brain. Minocycline has characteristics conferring neuroprotection. Current study evaluates the role of the CREB‐BDNF signaling pathway in mediating minocycline's neuroprotective effects against alcohol‐induced neurodegeneration. Seventy adult male rats were randomly split into groups 1 and 2 that received saline and alcohol (2 g/kg/day by gavage, once daily), respectively, and groups 3, 4, 5, and 6 were treated simultaneously with alcohol and minocycline (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 88 publications
4
13
0
Order By: Relevance
“…A previous study found that LPS-induced depression-like behaviour in mice by decreasing CREB and BDNF expressions in the prefrontal cortex (PFC) and hippocampus [ 4 ]. Minocycline treatment can protect methylphenidate- [ 34 ] and alcohol- [ 24 ] induced neurodegeneration in the rat brain by upregulating CREB and BDNF expressions. In a rat model of chronic, unpredictable, stress-induced depression, memantine treatment was shown to have an antidepressant-like effect by preventing hippocampus mitochondrial dysfunction and memory impairment via the upregulation of the CREB/BDNF signalling pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that LPS-induced depression-like behaviour in mice by decreasing CREB and BDNF expressions in the prefrontal cortex (PFC) and hippocampus [ 4 ]. Minocycline treatment can protect methylphenidate- [ 34 ] and alcohol- [ 24 ] induced neurodegeneration in the rat brain by upregulating CREB and BDNF expressions. In a rat model of chronic, unpredictable, stress-induced depression, memantine treatment was shown to have an antidepressant-like effect by preventing hippocampus mitochondrial dysfunction and memory impairment via the upregulation of the CREB/BDNF signalling pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the developing research has been focusing on its neuroprotective properties in in vivo and in vitro animal models, as well as in clinical studies [ 21 , 22 ]. Recent studies have shown that minocycline can improve synaptic transmission and integrity, as well as neurologic function via reductions in phosphorylated tau protein levels and the upregulation of BDNF/CREB signalling pathways in several animal models [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, adult rats treated with clozapine, a treatment for schizophrenia and bipolar disorder, showed upregulation of both iPLA2 and BDNF messages and protein (Kim et al, 2012). Furthermore, in adult animal models, repetitive or semichronic alcohol exposures (sometimes at unspecified BACs) have been linked to brain BDNF reductions (Davis, 2008; Motaghinejad et al, 2021; Palmisano & Pandey, 2017; Xu et al, 2015). Consequently, a reasonable hypothesis to be tested in our semi‐chronic binge model emerges: moderate BACs trigger depletion of both brain BDNF and linked iPLA2 levels that are thwarted by DHA supplementation, such that BDNF might thus be a key DHA‐responsive modulator of molecular events facilitating iPLA2 normalization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the developing research is focusing on its neuroprotective properties in in vivo and in vitro animal models as well as in clinical studies. Recent studies showed that minocycline improved synaptic transmission and integrity as well as neurologic function via reduction of phosphorylated tau protein level and upregulation of BDNF/CREB signalling pathways in several animal models (Motaghinejad et al, 2021;Salehi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%